Improving the Performance of PbS Quantum Dot Solar Cells by Optimizing ZnO Window Layer - Yang, Xiaokun; Hu, Long; Deng, Hui; Qiao, Keke; Hu, Chao; Liu, Zhiyong; Yuan, Shengjie; Khan, Jahangeer; Li, Dengbing; Tang, Jiang; Song, Haisheng; Cheng, Chun (Nano-Micro Letters, 2017)
Comparing with hot researches in absorber layer, window layer has attracted less attention in PbS quantum dot solar cells (QD SCs). Actually, the window layer plays a key role in exciton separation, charge drifting, and so on. Herein, ZnO window layer was systematically investigated for its roles in QD SCs performance. The physical mechanism of improved performance was also explored. It was found that the optimized ZnO films with appropriate thickness and doping concentration can balance the optical and electrical properties, and its energy band align well with the absorber layer for efficient charge extraction. Further characterizations demonstrated that the window layer optimization can help to reduce the surface defects, improve the heterojunction quality, as well as extend the depletion width. Compared with the control devices, the optimized devices have obtained an efficiency of 6.7% with an enhanced V oc of 18%, J sc of 21%, FF of 10%, and power conversion efficiency of 58%. The present work suggests a useful strategy to improve the device performance by optimizing the window layer besides the absorber layer. Highlights: 1 The efficiencies of PbS solar cells was significantly improved from 4.3% to 6.7% by optimizing ZnO window layer. 2 Optimized ZnO window layer can reduce the surface defects, extend thedepleted-heterojunction width and align with energy band of absorber layer.